Analysis of the Multi-Factor Evaluation Process Method in the Decision of Choosing Asuransi Jiwa Syariah Bumiputera Branch Medan - Torong, Laura Oktarani Br; Batubara, Chuzaimah (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Insurance products are financial instruments used to anticipate the risk of financial loss that may occur in life. Choosing a life insurance product that suits the needs of prospective customers requires the right method to increase efficiency with appropriate product suitability information, to facilitate prospective customers in making decisions about choosing sharia life insurance products that are in accordance with the conditions of prospective customers based on several factors, namely age, insurance premiums, benefits, payment period and method of payment. The Multi-Factor Evaluation Process (MFEP) method is used to facilitate decision-making so that it is more accurate, efficient, and effective. The results of the ranking in this study are the ranking of Sharia life insurance products that are recommended for prospective customers, sorted from the highest to the lowest evaluation weight value. Based on calculations performed using the Multi-Factor Evaluation Process (MFEP) method, Mitra Iqra’ Plus Products received a score of 2.60, Mitra Mabrur Plus received a score of 2.40, and AJSB Assalam Family received the highest score of 3.40. It can be concluded that the AJSB Assalam Family product is a product that is recommended to customers.